The Model of Madrasah Labor Based on Local Wisdom and an Integration of Tradition and Education - Rahmawati Rahmawati; Suci Ramadhanti Febriani; Khadijah Khadijah; Prayoga Saputra (AT-TA'LIM, 2024)
This research aims to identify the Madrasah labor model at the Tarbiyah and Teacher Training Faculty of UIN Imam Bonjol Padang by adopting three Madrasahs at Adabiyah, Diniyah Putri College and Sumatra Thawalib Padang Panjang College. This research uses a qualitative research design and uses descriptive analysis methods. Data collection techniques include interviews, observation and documentation. The results of the research show that the form of local wisdom and school development strategy at Adabiyah is through the integration of local wisdom by internalizing Minangkabau philosophical values in learning, while at the Diniyah Puteri Padang Panjang college internalizing local wisdom in the form of internalizing a typical local curriculum related to the affective values of a woman Minang. The Madrasah labor model that is suitable for the Tarbiyah and Teacher Training Faculty of UIN Imam Bonjol is a Madrasah labor developed on the basis of local culture and wisdom. Culture and local wisdom-based Madrasahs are a Madrasah model organized to meet national education standards that are enriched with comparative and competitive advantages based on noble cultural values so that students can learn actively to develop all their potential.